CHALLENGES AND STRATEGIES IN IMPLEMENTING INCLUSIVE EDUCATION: A META- ANALYSIS OF GLOBAL PERSPECTIVES - Loso Judijanto; Al-Amin (Indonesian Journal of Education (INJOE), 2024)
Inclusive education has become a major focus of global education policy, but its implementation still faces complex challenges. The main challenges identified include a lack of understanding of the concept of inclusion, limited resources and infrastructure, lack of teacher skills in dealing with student diversity, policy and system barriers, and social stigma and discrimination. To address these challenges, various strategies have been developed and implemented in different countries. These strategies include increasing public awareness and understanding, developing supportive policies, improving teacher capacity through training, providing adequate resources, and collaboration between various stakeholders. Although challenges remain, many countries have shown significant progress in implementing inclusive education. Thus, a holistic and contextualised approach that considers each country's social, cultural and economic conditions is necessary to achieve effective and sustainable implementation of inclusive education